PROGRAMING PLC CONTROLLER WITH LADDER DIAGRAM (Balkan Journal of Applied Mathematics and Informatics, 2023)
In this paper are consider one industrial process and consider about the automation of that industrial process. In automation the most important part is the controller. The controller is actually the brain of the process, and it regulates the switching on and off of all the elements involved in the process itself. The controllers that are used in industrial automation are called programmable logic controllers (PLC controllers). With example is showed how the PLC controller can be programed with Ladder Diagram. PLC programming involves creating a set of instructions that govern the behavior of a PLC to control machinery and processes. These instructions are written using specialized software tools and are executed in a sequential manner. The primary objectives of PLC programming are to ensure the safe and efficient operation of automated systems, maintain process accuracy, and facilitate quick responses to changing conditions.